2010
DOI: 10.1055/s-0030-1255778
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection for gastric lesions: results of an European inquiry

Abstract: ESD in Europe seems to be performed at a few centers, with most endoscopists performing a low number of procedures, achieving a high rate of efficacy and a moderate rate of major complications. However, as a potential selection bias may have occurred, multicenter registries should be conducted to help address the problem of dissemination of this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 14 publications
1
24
1
2
Order By: Relevance
“…The median total procedure time was 74 minutes, which is comparable to other published data with different devices. [2][3][4]23,24 Compared with Western studies using ESD, our procedure time was less than previously reported in these studies: the median procedure times were 85 minutes, 22 108 minutes, 11 and 161 minutes. 10 Compared with EMR, the ESD procedure time is significantly longer.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The median total procedure time was 74 minutes, which is comparable to other published data with different devices. [2][3][4]23,24 Compared with Western studies using ESD, our procedure time was less than previously reported in these studies: the median procedure times were 85 minutes, 22 108 minutes, 11 and 161 minutes. 10 Compared with EMR, the ESD procedure time is significantly longer.…”
Section: Discussioncontrasting
confidence: 53%
“…[3][4][5] A few small series also were reported from Western countries. [6][7][8][9][10][11] However, ESD has not yet been standardized, and it is technically difficult, time consuming, and potentially hazardous. 7 The aim of this study was to evaluate the efficacy and safety of ESD by use of a new water jet-assisted ESD (WESD) system in patients with early gastric neoplastic lesions.…”
mentioning
confidence: 99%
“…In all, 11 of the 15 specimens were resected en bloc. Compared to other Western series (22), an en bloc resection rate of 73% in this study is acceptable and can be improved by always retrieving the specimen in a basket instead of with forceps, as we did in some cases. The reason why the R0 resection rate was higher than the en bloc rate is that two specimens were divided into two parts during retrieval.…”
Section: Discussionmentioning
confidence: 47%
“…Una encuesta europea reciente entre 58 endoscopistas europeos (de un total de 490) detectó una media de 4 disecciones submucosas gástricas por endoscopista y año (en el último año previo a la encuesta). De un total de 510 disecciones gástricas registradas, se alcanzó un 77% de resecciones completas con un 13% de complicaciones (hemorragia y perforación en el 8 y 5% de los casos, respectivamente) 152 . De este estudio, a pesar de la baja tasa de participación (12%) que puede introducir un sesgo de selección, se debe destacar que a pesar del escaso número de disecciones efectuadas por endoscopista y año, se consiguen unas elevadas tasas de resección completa con un razonable porcentaje de complicaciones mayores.…”
Section: Expansión De La Dse En Occidenteunclassified